Skupljači perja - Petrović, Aleksandar (Serbia ; Croatia : Avala Film, 1967)
The protagonist, Beli Bora Perjar is a charming but mean-spirited gypsy, while his former affair, the kafana singer Lenče, is submissive. Bora is in love with the younger Tisa, who is being offered in marriage by her step-father. The two get themselves in trouble and eventually have to flee. Tisa rejects her husband and she and Bora get married in the church. Tisa tries to get to Belgrade, while Bora stabs a man in a knife fight. They are both, therefore, exiled from their Romani camp, yet their adventures continue.
Romology Film Collection
Keywords: Fiction films